Taming Indian Inflation - Cashin, Paul (International Monetary Fund, 2016)
High and persistent inflation has presented serious macroeconomic challenges in India in recent years, increasing the country's domestic and external vulnerabilities. A number of factors underpin India's high inflation. This book analyzes various facets of Indian inflation-the causes, consequences, and policies being implemented to manage it. Several chapters are devoted to analyzing and managing food inflation, given its significance in driving overall inflation dynamics in India.